Phytochemical Screening and Antidengue Activity of Jatropha Multifida Extract against DENV-2 - Mia Munawaroh Yuniyanti; Dwi Aris Agung Nugrahaningsih; Mae Sri Hartati Wahyuningsih (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Cases of dengue infection are still high in various parts of the world and no antiviral has been found to treat dengue infection. Jatropha multifida is one of the herbs used by the community to treat dengue infection, but pre-clinical and clinical scientific evidence has not been carried out. Phytochemical screening of ethanol extract of Jatropha multifida leaves was carried out using thin layer chromatography. Cytotoxic assay was performed on Vero cells using the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide). The cytotoxic concentration 50 (CC50) was determined using probit analysis. Anti-dengue test on dengue virus serotype 2 (DENV-2) was performed on Vero cells and the RNA (ribonucleic acid) copy number was quantified using quantitative polymerase chain reactions ((qPCR). Phytochemical screening results showed that the ethanol extract of Jatropha multifida leaves contains flavonoid and terpenoid compounds. CC50 of the extract was found to be 651.8 µg/mL. The RNA copy number of the treated group was lower than the control group and the difference was significant. The ethanol extract of Jatropha multifida leaves has anti-dengue activity against DENV-2.